The Correlation Between Knowledge of Pregnant Women and the Incidence of Anemia in Pregnancy in the Working Area of Puskesmas Nagrak - Susanti, Elsa; Novryanthi, Dhinny; Andriani, Ria (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Anemia in pregnancy is a global health issue with a prevalence of 48.9% in Indonesia (Riskesdas, 2018). This condition is influenced by iron deficiency (50% of cases), dietary patterns, and socioeconomic factors. Previous studies indicate a correlation between maternal knowledge and anemia incidence, yet research in the Puskesmas Nagrak area remains limited. Objective: To identify the relationship between pregnant women's knowledge and anemia incidence in the working area of Puskesmas Nagrak. Methods: A quantitative cross-sectional study involving 70 pregnant women in trimesters 1-3. Data were collected using Guttman-scale questionnaires and secondary data from maternal health records. Chi-Square test (a=0.05) was used for analysis. Results: 52.9% of respondents had anemia (Hb<11 g/dL). Women with low knowledge (38.6%) showed the highest anemia risk (p<0.000). Education level (57.1% junior high graduates) and occupation (92.9% housewives) significantly contributed. Conclusion: Knowledge level significantly affects anemia incidence. Community-based health education interventions are recommended to improve immunization coverage and Fe tablet consumption.